APLIKASI SIFAT GOLONGAN ULU AL-ALBAB DAN FASIK DI ERA SOCIETY 5.0: (Analisis Terhadap QS. Al-Ra’d/13:19-25) - Widodo, Panggih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
This study discusses the application of the ul? al-alb?b and wicked groups in the era of society 5.0 based on QS. al-Ra'd/13:19-25. This research is a library research using primary and secondary data with interpretation and sociology approaches. The results of this study are first, that the ul? al-alb?b group in QS. al-Ra'd/13:19-25 has several characteristics, namely taking lessons from everything, fulfilling promises, connecting something that is ordered to be connected, fearing painful reckoning, being patient, establishing prayer, giving alms, and repaying evil with good. Second, the wicked group in the verse are breaking promises, breaking something that is ordered to be continued, and doing damage. The three forms of application of the ul? al-alb?b group in QS. al-Ra'd/13:19-25 in the era of society 5.0, among others, using the internet wisely, as a means of connecting, as a means of giving alms, and as a means of spreading goodness. Meanwhile, the application of the wicked groups in this verse in the era of society 5.0 includes using the internet for immorality, breaking social relations or hospitality, and using it to do damage. The urgency of this research is to provide understanding to Muslims about the characteristics of ul? al-alb?b and wicked, so that they can be used to face the era of society 5.0.